Positive electrode material, positive electrode plate, secondary battery and electric device
By using the combination of large particles and small particles in the lithium iron phosphate positive electrode material to adjust the particle size and carbon content, the problem of difficult to take into account both energy density and circulation performance in the prior art is solved, and the high energy density and long circulation life of the battery are achieved.
Patent Information
- Application Number
- CN202410177919.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-08
- Publication Date
- 2025-04-18
AI Technical Summary
The existing lithium iron phosphate positive electrode materials are difficult to take into account good cycling performance while increasing the energy density.
The combination of large-particle lithium iron phosphate and small-particle lithium iron phosphate is adopted to improve the compaction density and dynamic performance of the electrode sheet by adjusting the particle size and carbon content, thereby improving the energy density and cycle life of the battery.
The battery has a high energy density and a longer cycle life, solving the problem of loss of cycle performance when lithium iron phosphate positive electrode material increases energy density.
Smart Images

Figure CN119852345A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a positive electrode material, a positive electrode sheet, a secondary battery and an electrical device. Background Art
[0002] In recent years, as the application scope of lithium-ion batteries has become more and more extensive, lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As lithium-ion batteries have made great progress, higher requirements have been put forward for their energy density, cycle performance and safety performance.
[0003] As a positive electrode material for lithium-ion batteries, lithium iron phosphate has quickly become a global research hotspot due to its abundant resources, low price, environmental friendliness, and stable voltage in two-phase reactions. Since the specific capacity of lithium iron phosphate is lower than that of ternary materials, in recent years, people have mainly focused on improving the capacity of lithium iron phosphate as a research and development hotspot. However, focusing only on improving the capacity performance of lithium iron phosphate will inevitably lose other battery properties, such as cycle performance. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode material, the battery prepared by the positive electrode material can have both good energy density and cycle performance.
[0005] In order to achieve the above-mentioned purpose, the first aspect of the present application provides a positive electrode material, comprising first lithium iron phosphate salt particles and second lithium iron phosphate salt particles, the primary average particle size of the first lithium iron phosphate salt particles is 500nm~3000nm, and the carbon content of the second lithium iron phosphate salt particles is 1.5wt%-2.0wt% calculated based on the total weight of the second lithium iron phosphate salt particles, and the mass of the second lithium iron phosphate salt particles is greater than or equal to the mass of the first lithium iron phosphate salt particles.
[0006] In the positive electrode material provided in the present application, a combination of large-particle lithium iron phosphate (first lithium iron phosphate salt particles) and small-particle lithium iron phosphate (second lithium iron phosphate salt particles) is used, which can effectively improve the compaction density of the pole piece, thereby improving the energy density of the battery cell. In addition, large-particle lithium iron phosphate has good kinetic performance, high gram capacity, good crystallinity, and excellent cycle performance; and small-particle lithium iron phosphate also has excellent cycle performance. Therefore, the combination of large-particle lithium iron phosphate and small-particle lithium iron phosphate can enable the battery cell to have both high energy density and longer cycle life.
[0007] In the positive electrode material provided in the present application, the small-particle lithium iron phosphate used maintains a relatively high carbon content, which can not only improve the electronic conductivity of the material, but also help to hide part of the initial capacity of the positive electrode material, thereby enabling the battery to have a longer cycle life.
[0008] In the positive electrode material provided in the present application, the mass of small-particle lithium iron phosphate is kept greater than or equal to the mass of large-particle lithium iron phosphate. That is, by mixing a small amount or an equal amount of large-particle lithium iron phosphate into long-cycle small-particle lithium iron phosphate, the technical problem that energy density and long cycle cannot be taken into account at the same time can be effectively improved, thereby maintaining its long cycle performance while improving the battery energy density.
[0009] In any embodiment, the mass ratio of the second lithium iron phosphate salt particles to the first lithium iron phosphate salt particles is 1:1 to 8:1.
[0010] When the mass ratio of large-particle lithium iron phosphate to small-particle lithium iron phosphate is controlled within the range of 1:1 to 8:1, the compaction density of the positive electrode sheet can be further improved, thereby further improving the energy density and cycle performance of the battery.
[0011] In any embodiment, the primary average particle size of the second lithium iron phosphate salt particles is 50 nm to 400 nm.
[0012] In any embodiment, the primary average particle size of the first lithium iron phosphate salt particles is 650 nm to 920 nm.
[0013] In any embodiment, based on the total weight of the first lithium iron phosphate salt particles, the carbon content of the first lithium iron phosphate salt particles is 0.8 wt % to 1.5 wt %.
[0014] When the carbon content of large-particle lithium iron phosphate is controlled to be lower than that of small-particle lithium iron phosphate, a lower specific surface area and a higher capacity can be maintained, thereby further improving the energy density of the battery; at the same time, large-particle lithium iron phosphate can also hide part of the initial capacity of the positive electrode active material, thereby further improving the long cycle life of the battery.
[0015] In any embodiment, the second lithium iron phosphate salt particle includes a core and a carbon coating layer on at least a portion of the surface of the core.
[0016] In any embodiment, the carbon coating layer includes a first carbon coating layer and a second carbon coating layer, and the first carbon coating layer is located between the inner core and the second carbon coating layer.
[0017] After the surface of lithium iron phosphate is coated with a high amount of carbon, the conductivity of the material can be further improved, thereby further improving the dynamic performance.
[0018] In any embodiment, the BET specific surface area of the first lithium iron phosphate particles is 3 m 2 / g~8m 2 / g; and / or, the BET specific surface area of the second lithium iron phosphate particles is less than or equal to 18.5m 2 / g.
[0019] When the BET specific surface area of large-particle lithium iron phosphate and small-particle lithium iron phosphate is controlled within the above range, it is beneficial to increase the contact area between the positive electrode material and the electrolyte, so that the electrochemical activity of the positive electrode material is further enhanced.
[0020] In any embodiment, the molecular formulas of the first lithium iron phosphate salt particles and the second lithium iron phosphate salt particles are independently Li m Fe x P y O j Q q , wherein Q includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.95≤m≤1.15, 0.9≤x≤1, 0.95≤y≤1, 3.5≤j≤4, and 0<q≤0.1.
[0021] In any embodiment, the Q includes at least one of Ti, V, Mg, and Nb, and the content of Q in the first lithium iron phosphate salt particles is 4000ppm-10000ppm based on the total weight of the first lithium iron phosphate salt particles; and / or, the content of Q in the second lithium iron phosphate salt particles is 1000ppm-3000ppm based on the total weight of the second lithium iron phosphate salt particles.
[0022] When the content of Q element in large-particle lithium iron phosphate and small-particle lithium iron phosphate is controlled within the above range, the gram capacity of the positive electrode material can be further improved, so that the prepared battery has a better energy density.
[0023] In any embodiment, the positive electrode material is single crystal particles and / or polycrystalline particles.
[0024] In any embodiment, the capacity proportion η of the first lithium iron phosphate salt particles is ≥ 88%, and η is defined as: a battery containing the first lithium iron phosphate salt particles as a positive electrode material is charged and discharged twice at a constant current rate of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current rate of 1C. In the charge and discharge test at the rate of 1C, the capacity value extracted when the discharge voltage is 3.2V is recorded as C1, and the capacity value extracted when the discharge voltage is to 2.0V is C2, η = C1 / C2, wherein the charging process includes constant voltage charging, a constant voltage of 3.75V, and a constant voltage cut-off current of 50μA.
[0025] When the capacity ratio of the first lithium iron phosphate salt particles has the above characteristics, the energy density and cycle performance of the battery can be further improved.
[0026] The second aspect of the present application provides a positive electrode plate, characterized in that it includes a positive electrode collector and a positive electrode material arranged on at least one surface of the positive electrode collector, wherein the positive electrode material is the positive electrode material described in the first aspect of the present application.
[0027] In any embodiment, the surface density of the positive electrode active material on one side of the positive electrode sheet is 20.0 mg / cm 2 -35.0mg / cm 2 .
[0028] By coating the positive electrode active material thickly on the surface of the positive electrode plate, the battery cell can achieve a higher volume energy density; at the same time, when the surface density of the positive electrode active material on the positive electrode plate is controlled within a certain range, the battery energy density and cycle performance can be improved at the same time.
[0029] In any embodiment, the compaction density of the positive electrode active material layer on the positive electrode sheet is 2.30 g / cm 3 -2.70g / cm 3 .
[0030] When the electrode compaction density is controlled within a certain range, the battery can maintain a higher energy density.
[0031] The third aspect of the present application provides a secondary battery, characterized in that it includes the positive electrode sheet described in the third aspect of the present application.
[0032] A fourth aspect of the present application provides an electrical device, comprising the secondary battery described in the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0034] Figure 2 yes Figure 1An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0035] Figure 3 Schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.
[0036] Description of reference numerals:
[0037] 5 secondary battery; 51 housing; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0038] Hereinafter, embodiments of the positive electrode material, the positive electrode sheet containing the positive electrode material, the secondary battery, the electric device and the method for manufacturing the same of the present application are described in detail. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0039] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0040] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0041] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0042] If not otherwise specified, all steps of the present application may be performed sequentially or randomly, and may be performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0043] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0044] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0045] Due to the structural characteristics of lithium iron phosphate, the electronic and ionic conductivity of the bulk phase of the material is low, and carbon coating and particle nano-sizing are generally required to improve the electrical conductivity and ionic conductivity. However, nano-sizing and surface carbon coating will lead to low compaction density of lithium iron phosphate materials, thereby affecting the energy density of lithium iron phosphate materials. With the development of the market, the requirements for the range and low cost of lithium iron phosphate vehicles are increasing, and the demand for high energy density and long cycle power batteries is increasing.
[0046] [Cathode material]
[0047] In order to achieve the above-mentioned object, the present application provides a positive electrode material, comprising first lithium iron phosphate salt particles and second lithium iron phosphate salt particles.
[0048] In some embodiments, the primary average particle size of the first lithium iron phosphate salt particles is 500 nm to 3000 nm.
[0049] In some preferred embodiments, the primary average particle size of the first lithium iron phosphate salt particles is 650 nm to 920 nm, such as 650 nm, 870 nm, 920 nm, etc., or other unlisted values within the range of 650 nm to 920 nm.
[0050] In some embodiments, the primary average particle size of the second lithium iron phosphate salt particles is 50 nm to 400 nm.
[0051] In some preferred embodiments, the primary average particle size of the second lithium iron phosphate salt particles is 150 nm to 250 nm, such as 150 nm, 250 nm, etc., or other unlisted values within the range of 150 nm to 250 nm.
[0052] In the positive electrode material provided in the present application, a combination of large-particle lithium iron phosphate (first lithium iron phosphate salt particles) and small-particle lithium iron phosphate (second lithium iron phosphate salt particles) is used, which can effectively improve the compaction density of the pole piece, thereby improving the energy density of the battery cell. In addition, large-particle lithium iron phosphate has good kinetic performance, high gram capacity, good crystallinity, and excellent cycle performance; and small-particle lithium iron phosphate also has excellent cycle performance. Therefore, the combination of large-particle lithium iron phosphate and small-particle lithium iron phosphate can enable the battery cell to have both high energy density and longer cycle life.
[0053] In some embodiments, the mass of the second lithium iron phosphate salt particles is greater than or equal to the mass of the first lithium iron phosphate salt particles.
[0054] In the positive electrode material provided in the present application, the mass of small-particle lithium iron phosphate is kept greater than or equal to the mass of large-particle lithium iron phosphate. That is, by mixing a small amount or an equal amount of large-particle lithium iron phosphate into long-cycle small-particle lithium iron phosphate, the technical problem that energy density and long cycle cannot be taken into account at the same time can be effectively improved, thereby maintaining its long cycle performance while improving the battery energy density.
[0055] In some preferred embodiments, the mass ratio of the second lithium iron phosphate salt particles to the first lithium iron phosphate salt particles is 1:1 to 8:1, for example, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, etc., or other values not listed in the range of 1:1 to 8:1. In some more preferred embodiments, the mass ratio of the second lithium iron phosphate salt particles to the first lithium iron phosphate salt particles is 1:1, 3:1, 4:1, 7:1, 8:1, or other values not listed in the range of 1:1 to 8:1.
[0056] When the mass ratio of large-particle lithium iron phosphate to small-particle lithium iron phosphate is controlled within the range of 1:1 to 8:1, the compaction density of the positive electrode sheet can be further improved, thereby further improving the energy density and cycle performance of the battery.
[0057] In some embodiments, based on the total weight of the second lithium iron phosphate salt particles, the carbon content of the second lithium iron phosphate salt particles is 1.5 wt % to 2.0 wt %.
[0058] In some preferred embodiments, based on the total weight of the second lithium iron phosphate salt particles, the carbon content of the second lithium iron phosphate salt particles is 1.55 wt%-1.95 wt%, for example, 1.55 wt%, 1.70 wt%, 1.85 wt%, 1.95 wt%, etc., or other unlisted values within the range of 1.55 wt%-1.95 wt%.
[0059] In the positive electrode material provided in the present application, the small-particle lithium iron phosphate used maintains a relatively high carbon content, which can not only improve the electronic conductivity of the material, but also help to hide part of the initial capacity of the positive electrode material, thereby enabling the battery to have a longer cycle life.
[0060] In some embodiments, based on the total weight of the first lithium iron phosphate salt particles, the carbon content of the first lithium iron phosphate salt particles is 0.8 wt%-1.5 wt%, for example, 0.8 wt%, 1.2 wt%, 1.35 wt%, 1.5 wt%, etc., or other unlisted values within the range of 0.8 wt%-1.5 wt%.
[0061] When the carbon content of large-particle lithium iron phosphate is controlled to be lower than that of small-particle lithium iron phosphate, a lower specific surface area and a higher capacity can be maintained, thereby further improving the energy density of the battery; at the same time, large-particle lithium iron phosphate can also hide part of the initial capacity of the positive electrode active material, thereby further improving the long cycle life of the battery.
[0062] As used in this article, the determination method of "carbon content" is based on the standard GB / T 20123-2006 / ISO 15350:2000, using a carbon-sulfur analyzer.
[0063] As used herein, "carbon content" refers to the presence of carbon in the lithium iron phosphate particles, which may be mixed with the lithium iron phosphate particles or coated on the lithium iron phosphate particles. In some preferred embodiments, "carbon content" refers to the state in which the carbon in the lithium iron phosphate particles is coated on the lithium iron phosphate particles, thereby enabling the carbon to form a uniform and dense carbon coating layer on the surface of the lithium iron phosphate particles, thereby improving the surface conductivity of the particles.
[0064] In some preferred embodiments, the second lithium iron phosphate salt particle comprises a core and a carbon coating layer on at least a portion of the surface of the core.
[0065] In some more preferred embodiments, the carbon coating layer includes a first carbon coating layer and a second carbon coating layer, and the first carbon coating layer is located between the inner core and the second carbon coating layer.
[0066] As used herein, "carbon coating layer" refers to the portion coated on the lithium iron phosphate particles, which may but does not necessarily completely coat the lithium iron phosphate particles. The use of "carbon coating layer" is only for ease of description and is not intended to limit the present application.
[0067] After the surface of lithium iron phosphate is coated with a high amount of carbon, the conductivity of the material can be further improved, thereby further improving the dynamic performance.
[0068] In some embodiments, the BET specific surface area of the first lithium iron phosphate particles is 3 m 2 / g~8m 2 / g.
[0069] In some preferred embodiments, the BET specific surface area of the first lithium iron phosphate particles is 3 m 2 / g~7.5m 2 / g, for example 3m 2 / g, 6m 2 / g, 7m 2 / g, 7.5m 2 / g, etc., or 3m 2 / g~7.5m 2 / Other values not listed in the g range.
[0070] In some embodiments, the BET specific surface area of the second lithium iron phosphate particles is less than or equal to 18.5 m 2 / g.
[0071] In some preferred embodiments, the BET specific surface area of the second lithium iron phosphate particles is less than or equal to 13-18 m 2 / g, for example 13m 2 / g, 15m 2 / g, 16m 2 / g, 18m 2 / g, etc., or 13-18m 2 / Other values not listed in the g range.
[0072] As used herein, "specific surface area" or "BET" refers to the total area per unit mass of a material.
[0073] When the BET specific surface area of large-particle lithium iron phosphate and small-particle lithium iron phosphate is controlled within the above range, it is beneficial to increase the contact area between the positive electrode material and the electrolyte, so that the electrochemical activity of the positive electrode material is further enhanced.
[0074] In some embodiments, the molecular formulas of the first lithium iron phosphate salt particles and the second lithium iron phosphate salt particles are independently Li m Fe x P y O j Q q , wherein Q includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.95≤m≤1.15, 0.9≤x≤1, 0.95≤y≤1, 3.5≤j≤4, and 0<q≤0.1.
[0075] In this article, when a substance has a "molecular formula", the substance is not limited to the substance represented by the molecular formula, but also includes other substances formed by further doping and / or coating modification based on the molecular formula, which is not limited here. The use of "molecular formula" is only for the convenience of description and is not intended to limit this application.
[0076] In some embodiments, the Q includes at least one of Ti, V, Mg, and Nb.
[0077] In some preferred embodiments, Q comprises Ti.
[0078] In some embodiments, based on the total weight of the first lithium iron phosphate salt particles, the content of Q in the first lithium iron phosphate salt particles is 4000 ppm-10000 ppm.
[0079] In some preferred embodiments, based on the total weight of the first lithium iron phosphate salt particles, the content of Q in the first lithium iron phosphate salt particles is 5000ppm-6000ppm, for example, 5000ppm, 6000ppm, or other unlisted values within the range of 5000ppm-6000ppm.
[0080] In some embodiments, based on the total weight of the second lithium iron phosphate salt particles, the content of Q in the second lithium iron phosphate salt particles is 1000 ppm-3000 ppm.
[0081] In some preferred embodiments, based on the total weight of the second lithium iron phosphate salt particles, the content of Q in the second lithium iron phosphate salt particles is 1500ppm-2100ppm, for example, 1500ppm, 2100ppm, or other unlisted values within the range of 1500ppm-2100ppm.
[0082] When the content of Q element in large-particle lithium iron phosphate and small-particle lithium iron phosphate is controlled within the above range, the gram capacity of the positive electrode material can be further improved, so that the prepared battery has a better energy density.
[0083] In some embodiments, the positive electrode material is single crystal particles and polycrystalline particles.
[0084] In some embodiments, the cathode material is a single crystal particle or a polycrystalline particle. In some embodiments, the cathode material is a single crystal particle. In some embodiments, the cathode material is a polycrystalline particle.
[0085] In some embodiments, the capacity proportion η of the first lithium iron phosphate salt particles is ≥ 88%.
[0086] In some preferred embodiments, the capacity proportion η of the first lithium iron phosphate salt particles is ≥89.2%, such as 89.2%, 91.3%, 92.1%, 92.2%, etc., or other unlisted values within the range of ≥89.2%.
[0087] The definition of η is: the battery containing the first lithium iron phosphate salt particles as the positive electrode material is charged and discharged twice at a constant current rate of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current rate of 1C. In the charge and discharge test at a rate of 1C, the capacity value extracted when the discharge voltage is 3.2V is recorded as C1, and the capacity value extracted when the discharge voltage is to 2.0V is recorded as C2, η=C1 / C2, wherein the charging process includes constant voltage charging, a constant voltage of 3.75V, and a constant voltage cut-off current of 50μA.
[0088] In some embodiments, the X-ray diffraction pattern of the second lithium iron phosphate salt particles tested in a fully charged state satisfies: a (311) crystal plane peak in the range of 35°-36°, a (011) crystal plane peak in the range of 20°-21°, and a ratio of the peak intensity I311 of the (311) crystal plane peak to the peak intensity I011 of the (011) crystal plane peak satisfies I311 / I011≥0.008.
[0089] When the capacity ratio of large-particle lithium iron phosphate has the above characteristics, or when the X-ray diffraction spectrum of small-particle lithium iron phosphate has the above characteristics, the energy density and cycle performance of the battery can be further improved.
[0090] The present application also provides a method for preparing a positive electrode material, characterized in that the positive electrode material comprises first lithium iron phosphate salt particles, and the manufacturing process of the first lithium iron phosphate salt particles comprises: providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and performing at least two sintering steps.
[0091] [Positive electrode]
[0092] The present application also provides a positive electrode plate, characterized in that it includes a positive electrode current collector and a positive electrode material arranged on at least one surface of the positive electrode current collector, wherein the positive electrode active material is the positive electrode material described in the present application, or the positive electrode material obtained according to the preparation method described in the present application.
[0093] In some embodiments, the surface density of the positive active material on one side of the positive electrode sheet is 20.0 mg / cm 2 -35.0mg / cm 2 , for example 22.0 mg / cm 2 、25.0mg / cm 2 、27.0mg / cm 2 、35.0mg / cm 2 etc., or 20.0mg / cm 2 -35.0mg / cm 2 Other values within the range not listed.
[0094] By coating the positive electrode active material thickly on the surface of the positive electrode plate, the battery cell can achieve a higher volume energy density; at the same time, when the surface density of the positive electrode active material on the positive electrode plate is controlled within a certain range, the battery energy density and cycle performance can be improved at the same time.
[0095] In some embodiments, the compaction density of the positive electrode active material layer on the positive electrode sheet is 2.30 g / cm 3 -2.70g / cm 3 .
[0096] In some preferred embodiments, the compaction density of the positive electrode active material layer on the positive electrode sheet is 2.30 g / cm 3 -2.68g / cm 3 , for example 2.30g / cm 3 , 2.38g / cm 3 , 2.41g / cm 3 , 2.44g / cm 3 , 2.50g / cm 3 , 2.51g / cm 3 , 2.53g / cm 3 , 2.56g / cm 3 , 2.58g / cm 3 , 2.61g / cm 3 , 2.68g / cm 3 etc., or 2.30g / cm 3 -2.68g / cm 3 Other values within the range not listed.
[0097] When used in this article, "compacted density" is defined as: compacted density = surface density / (thickness of the pole piece after rolling - thickness of the current collector), and its determination method can refer to GB / T24533-2009.
[0098] When the electrode compaction density is controlled within a certain range, the battery can maintain a higher energy density.
[0099] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0100] In some embodiments, the positive electrode plate may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0101] In some embodiments, the positive electrode plate may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0102] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0103] [Negative electrode]
[0104] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0105] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0106] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0107] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0108] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0109] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0110] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0111] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0112] [Electrolytes]
[0113] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs.
[0114] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0115] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0116] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0117] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0118] [Isolation film]
[0119] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0120] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0121] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0122] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0123] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0124] [Lithium secondary battery]
[0125] The present application also provides a lithium secondary battery, characterized in that it includes the positive electrode plate described in the present application.
[0126] The present application has no particular limitation on the shape of the lithium secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.
[0127] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0128] [Electrical devices]
[0129] In addition, the present application also provides an electrical device, the electrical device includes the lithium secondary battery provided in the present application. The lithium secondary battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0130] As the electrical device, a lithium secondary battery can be selected according to its usage requirements.
[0131] Figure 3 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the power consumption device's requirements for high power and high energy density of lithium secondary batteries, a battery pack or a battery module can be used.
[0132] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a lithium secondary battery may be used as a power source.
[0133] Example
[0134] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0135] 1. Preparation method
[0136] Example 1
[0137] (1) Preparation of positive electrode active material:
[0138] a) Preparation of the first lithium phosphate particles:
[0139] Weigh lithium carbonate, ferric oxide, phosphoric acid, glucose, titanium dioxide (based on the total weight of lithium iron phosphate particles, the amount of titanium dioxide added is such that the titanium content in the prepared lithium iron phosphate particles is 5000ppm) and polyaniline, wherein the weight ratio of Li element, Fe element and P element is such that Fe:P=0.968:1; Li:Fe=1:0.98, and the weight ratio of glucose to polyaniline is such that glucose:polyaniline=1:2. The amount of glucose and polyaniline added is such that after the first sintering, the carbon content accounts for 0.15% of the weight of the lithium iron phosphate precursor. Add water to the above substances to obtain a mixture slurry.
[0140] Use a ball mill to mix the mixture slurry evenly, grind it with a sand mill to obtain a slurry with a solid content of 38% and a Dv50 of 400nm, and spray dry it (the negative pressure of the high-speed spray dryer is -650 to -200Pa, the inlet temperature is 300℃ to 360℃, and the outlet temperature is 100℃ to 140℃). The dried reactants are loaded into a sintering furnace for the first sintering, and the heating rate is controlled at 5℃ / min, the insulation temperature is controlled at 650℃, and the insulation time is 4h. After the material is cooled, it is crushed by a mechanical mill to obtain a powder.
[0141] The obtained powder, glucose, polyaniline and water are mixed (based on the total weight of the lithium iron phosphate particles, the amount of glucose and polyaniline added is such that the carbon content of the product after the second sintering is 1.2%, and the weight ratio of glucose and polyaniline is such that glucose: polyaniline = 1:2), and the solid content is 40%. After uniform mixing, the slurry is obtained by ball milling and sand milling. The Dv50 of the insoluble matter in the slurry is 550nm. The slurry is spray dried (the negative pressure of the high-speed spray dryer is -650 to -200Pa, the inlet temperature is 300℃ to 360℃, and the outlet temperature is 100℃ to 140℃). The dried reactants are loaded into a sintering furnace for a second low-temperature sintering (the heating rate is controlled at 5℃ / min, the sintering temperature is 750℃, and the sintering time is 4h). After the material is cooled, it is crushed for the second time to an average particle size of 870 nm. After demagnetization, lithium iron phosphate salt particles are obtained, with a carbon content of 1.2% and a Ti content of 5000 ppm in the lithium iron phosphate salt particles.
[0142] b) Preparation of the second lithium phosphate particles:
[0143] FePO4, Li2CO3, the first carbon source glucose and titanium dioxide (based on the total weight of the lithium iron phosphate particles, the amount of titanium dioxide added satisfies the titanium content of the prepared lithium iron phosphate particles to be 1500ppm), wherein the weight ratios of Li element, Fe element and P element satisfy: Fe:P=0.965:1; Li:Fe=1:0.98, the amount of the first carbon source added is based on the total weight of the prepared positive electrode active material, the weight content of the residual carbon of the first carbon source (i.e., the weight content of the first carbon coating layer w1%) is 1.55%, mix them evenly, add a small amount of water thereto, grind to a volume distribution particle size Dv50 of 360nm, and then spray dry; place the spray-dried powder in a sintering furnace, heat to 770°C at 5°C / min in a nitrogen atmosphere and keep at this temperature for 10h, and obtain a lithium phosphate coated with the first carbon coating layer after cooling.
[0144] Take 8kg of lithium-containing phosphate coated with the first carbon coating layer (denoted as m) and place it in a rotary kiln, introduce nitrogen with a flow rate of 4L / min and throughout the heating process, insulation process and cooling process. Heat to 750°C at 5°C / min and keep warm for 25 minutes. During the insulation process, acetylene gas (deposition gas) is introduced with a gas flow rate V of 0.40L / min. After the insulation is completed, stop introducing acetylene gas, then cool naturally, and obtain LiFePO4 coated with two layers of carbon coating by air flow crushing. Based on the total weight of the prepared positive electrode active material, the weight content w2% of the second carbon coating layer is 0.15%. Finally, the second lithium phosphate particles with an average particle size of 250nm are obtained.
[0145] (2) Preparation of positive electrode slurry:
[0146] The first lithium phosphate salt particles and the second lithium phosphate salt particles are mixed at a mass ratio of 3:1 to obtain a positive electrode active material, the positive electrode active material, conductive carbon black, and binder polyvinylidene fluoride are mixed at a mass percentage of 96.0:2.0:2.0, and an appropriate amount of N-methylpyrrolidone is added, and the mixture is fully mixed, stirred, and dispersed to form a positive electrode slurry.
[0147] (3) Preparation of positive electrode sheet:
[0148] The viscosity of the mixed and stirred slurry is adjusted to 8000-20000 mPa.s until the slurry is not stratified, and the slurry is coated on the surface of the substrate Al foil by a double-sided double-control coating device, and then dried, cold pressed, slit, and sheeted to finally obtain the positive electrode sheet.
[0149] (4) Preparation of negative electrode sheet:
[0150] Artificial graphite, conductive carbon black, binder styrene-butadiene rubber (SBR) and thickener sodium carboxymethyl cellulose (CMC) are mixed evenly according to a mass percentage of 95:1.0:2.0:2.0, and a certain amount of deionized water is added, and the negative electrode slurry is obtained after stirring and dispersion, and the negative electrode slurry is coated on a substrate Cu foil, and the negative electrode sheet is obtained after drying, cold pressing, slitting and sheeting;
[0151] (4) Preparation of batteries:
[0152] Stack the positive electrode sheet, isolation film, and negative electrode sheet in order. The isolation film must be able to isolate the anode and cathode. The bare battery cell is obtained by winding, and the bare battery cell is placed in an outer package. The electrolyte is injected, and after packaging, formation, exhaust and other processes, a lithium-ion battery is finally obtained.
[0153] Embodiments 2 to 12
[0154] The secondary batteries of Examples 2 to 12 are prepared in a similar manner to that of Example 1, except that the carbon content, Ti content, primary average particle size, molecular formula, BET specific surface area, and capacity ratio η of the first lithium iron phosphate salt particles, or the carbon content, Ti content, primary average particle size, molecular formula, and BET specific surface area of the second lithium iron phosphate particles are adjusted, or the mass ratio of the first lithium iron phosphate salt particles to the second lithium iron phosphate salt particles is adjusted, or the surface density and compaction density of the positive electrode active material on the positive electrode sheet are adjusted. The different preparation parameters are detailed in Tables 1, 2, and 3.
[0155] Comparative Examples 1 to 3
[0156] The preparation methods of the secondary batteries of Comparative Examples 1 to 3 are similar to those of Example 1, but the primary average particle size of the first lithium iron phosphate salt particles is adjusted, or the carbon content of the second lithium iron phosphate salt particles is adjusted, or the mass ratio of the second lithium iron phosphate salt particles to the first lithium iron phosphate salt particles is adjusted. The different preparation parameters are detailed in Tables 1, 2, and 3.
[0157] 2. Performance Test
[0158] 1. Test methods for parameters related to positive electrode active materials
[0159] (1) Primary average particle size test method
[0160] The pole piece is cut open perpendicularly to the large surface of the pole piece by an argon ion beam to expose the cross section, which is photographed by a scanning electron microscope, and the longest diameter of the lithium iron phosphate salt particles is statistically analyzed by the long diameter statistical method. Among them, the "primary average particle size" refers to the average value of the primary particle size of all particles, which is numerically equal to the total particle size value divided by the total number of particles. Among them, the primary particle size in the cross-section diagram refers to the longest distance connected by two points on the edge. Specifically, the total number of lithium iron phosphate salt particles with a primary particle size greater than 50nm and the primary particle size of lithium iron phosphate salt particles with a primary particle size greater than 50nm can be counted in the electron microscope scanning photo, and the primary average particle size of the lithium iron phosphate salt particles = the primary particle size of the total lithium iron phosphate salt particles / the total number of lithium iron phosphate salt particles. Among them, in the above-mentioned particle size statistical process, particles with a primary average particle size less than or equal to 50nm are not included in the statistical range.
[0161] (2) Carbon content test method
[0162] Lithium iron phosphate is burned in a high-frequency induction furnace and then the carbon content is tested by infrared absorption method. The specific testing process is based on the standard GB / T 20123-2006 / ISO 15350:2000.
[0163] (3) Specific surface area test method
[0164] The specific surface area was tested by gas adsorption method according to the GB / T19587-2017 test standard, as follows: lithium iron phosphate granular salt was taken as a sample, the sample tube was immersed in liquid nitrogen at -196°C, and the adsorption amount of nitrogen on the solid surface at different pressures was measured at a relative pressure of 0.05-0.30. The monolayer adsorption amount of the sample was obtained based on the BET multilayer adsorption theory and its formula, thereby calculating the specific surface area of the material.
[0165] (4) Capacity ratio of the first lithium iron phosphate salt particle η
[0166] The preparation and testing process of the battery is as follows: 2.0000g of sample is mixed with 0.1111g of conductive carbon black and 0.1111g of PVDF (by mass ratio of 0.9:0.05:0.05), and then 2.5g of organic solvent NMP (N-methylpyrrolidone) is added, and after being fully mixed, a film with a thickness of 140 microns is coated on aluminum foil, vacuum dried at 120℃ for 2h, punched into 13mm discs using a puncher, pressed at 10Mpa using a tablet press, and kept in vacuum at 120℃ for 12h, and the weight of the positive electrode is weighed, wherein the loading amount of active material is 11-12mg. A button cell is assembled in an argon-protected glove box, with a metal lithium sheet as the negative electrode, an electrolyte of a mixed solvent of EC (ethylene carbonate) and DMC (1,2-dimethyl carbonate) in a volume ratio of 1:1, an electrolyte LiPF6, and a diaphragm of Celgard2400 microporous polyethylene film. Test the electrical performance of the assembled battery on a blue battery tester. In the voltage range of 2.0V to 3.75V, charge / discharge at 0.1C constant current for two weeks, and then charge / discharge at 1C constant current for two weeks to test the specific capacity. There is a constant voltage process during the charging process, the constant voltage is 3.75V, and the constant voltage cut-off current is 50uA.
[0167] A battery containing the lithium iron phosphate salt particles as the positive electrode material is charged and discharged twice at a constant current rate of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current rate of 1C. In the charge and discharge test at a rate of 1C, the capacity value at a discharge voltage of 3.2V is extracted and recorded as C1, and the capacity value at a discharge voltage of 2.0V is extracted as C2, η=C1 / C2, wherein the charging process includes constant voltage charging, a constant voltage of 3.75V, and a constant voltage cut-off current of 50uA.
[0168] 2. Test methods for parameters related to positive electrode
[0169] (1) Testing method of compaction density
[0170] The compaction density of the film layer on one side of the pole piece = m / (V1-V2), where m represents the weight of the film layer, V1 represents the volume of the pole piece, and V2 represents the volume of the current collector. m is obtained by subtracting the weight of the current collector from the weight of the pole piece. The product of the surface area of the pole piece and the thickness of the pole piece is the volume V1 of the pole piece, and the product of the surface area of the pole piece and the thickness of the current collector is V2. The thickness of the current collector and the thickness of the pole piece are obtained by measuring the thickness of the empty foil in the pole lug area with a micrometer.
[0171] (2) Surface density test method
[0172] The calculation formula of surface density = (electrode weight - electrode aluminum foil weight) / electrode area. Specifically, we can first weigh the mass and area of the aluminum foil, then weigh the mass and area of the electrode, and then subtract the surface density of the foil from the calculated surface density of the electrode to get the surface density of the dressing.
[0173] 3. Battery performance test method
[0174] (1) Cycle capacity retention rate
[0175] At 25±3℃, the battery cells were charged and discharged at constant power (0.5P / 0.5P, 2.5-3.65V), and the discharge capacity D at the 20th week was taken. 20 And 1000 cycle discharge capacity D 1000 The capacity retention rate can be obtained by comparing it with the discharge capacity D1 in the first week, that is: 20-week capacity retention rate = D 20 / D1*100%, 1000-cycle capacity retention rate = D 1000 / D1*100%.
[0176] (2) Energy density
[0177] Under 25±3℃ environment, the 0.5P discharge capacity (3.65-2.5V) of the battery cell was tested. The energy density (Wh / L) of the battery cell can be obtained according to the formula: Energy density = capacity * average voltage / battery cell volume.
[0178] III. Analysis of test results of various embodiments and comparative examples
[0179] The batteries of the embodiments and comparative examples were prepared according to the above method, and various performance parameters were measured. The results are shown in Table 3 below.
[0180] Table 1 Preparation parameters
[0181]
[0182] Table 2 Preparation parameters
[0183]
[0184] Table 3 Preparation parameters and performance parameters
[0185]
[0186] The positive electrode materials of Examples 1 to 12 all use first lithium iron phosphate salt particles and second lithium iron phosphate salt particles, wherein the primary average particle size of the first lithium iron phosphate salt particles is 500nm to 3000nm, wherein the carbon content of the second lithium iron phosphate salt particles is 1.5wt%-2.0wt%, and the mass of the second lithium iron phosphate salt particles is greater than or equal to the mass of the first lithium iron phosphate salt particles, so the secondary batteries prepared therefrom have both excellent energy density and cycle performance.
[0187] In the positive electrode material provided in the present application, the first lithium iron phosphate salt particles and the second lithium iron phosphate salt particles are used at the same time, which is beneficial to hide part of the initial capacity of the positive electrode material. Therefore, its capacity retention rate of 20 cycles at 25°C can reach more than 100%, thereby making the battery have a longer cycle life.
[0188] The mass of the second lithium iron phosphate salt particles of Comparative Example 1 is less than that of the first lithium iron phosphate salt particles.
[0189] From the comparison between Comparative Example 1 and Examples 1 to 12, it can be seen that the mass of the second lithium iron phosphate salt particles in the positive electrode material needs to be greater than or equal to the mass of the first lithium iron phosphate salt particles in order to effectively improve the energy density and cycle performance of the battery; and when the mass of the second lithium iron phosphate salt particles is less than the mass of the first lithium iron phosphate salt particles, it is not possible to effectively take into account both improving the energy density and cycle performance of the secondary battery.
[0190] In Comparative Example 2, the carbon content of the second lithium iron phosphate salt particles is the same as that of the first lithium iron phosphate salt particles, that is, the carbon content of the second lithium iron phosphate salt particles exceeds the range of 1.5 wt % to 2.0 wt %.
[0191] From the comparison between Comparative Example 2 and Examples 1 to 12, it can be seen that the carbon content of the second lithium iron phosphate salt particles in the positive electrode material needs to be controlled within the range of 1.5 wt%-2.0 wt% in order to effectively improve the energy density and cycle performance of the battery; and when the carbon content of the second lithium iron phosphate salt particles exceeds the range of 1.5 wt%-2.0 wt%, it is not possible to effectively take into account both improving the energy density and cycle performance of the secondary battery.
[0192] The primary average particle size of the first lithium iron phosphate salt particles of Comparative Example 3 exceeds the range of 500 nm to 3000 nm.
[0193] From the comparison between Comparative Example 3 and Examples 1 to 12, it can be seen that the primary average particle size of the first lithium iron phosphate salt particles in the positive electrode material needs to be controlled within the range of 500nm to 3000nm in order to effectively improve the energy density and cycle performance of the battery; and when the primary average particle size of the first lithium iron phosphate salt particles exceeds the range of 500nm to 3000nm, it is not possible to effectively take into account both the improvement of the energy density and the cycle performance of the secondary battery.
[0194] The mass ratio of the second lithium iron phosphate salt particles to the first lithium iron phosphate salt particles used in the positive electrode materials of Examples 1 to 12 is 1:1 to 8:1, and the secondary batteries prepared therefrom have both excellent energy density and cycle performance.
[0195] The primary average particle size of the second lithium iron phosphate salt particles used in the positive electrode materials of Examples 1 to 12 is 50 nm to 400 nm, and the secondary batteries prepared therefrom have both excellent energy density and cycle performance.
[0196] The manufacturing process of the first lithium iron phosphate salt particles in the positive electrode materials of Examples 1 to 12 includes: providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and performing at least two sinterings. The secondary batteries prepared thereby have both excellent energy density and cycle performance.
[0197] When the carbon content of the first lithium iron phosphate salt particles used in the positive electrode materials of Examples 1 to 12 is in the range of 0.8 wt % to 1.5 wt %, the secondary batteries prepared therefrom have both excellent energy density and cycle performance.
[0198] In the positive electrode materials of Examples 1 to 12, the second lithium iron phosphate salt particles used include a core and a carbon coating layer on at least a portion of the surface of the core, and the secondary batteries prepared therefrom have both excellent energy density and cycle performance.
[0199] The BET specific surface area of the first lithium iron phosphate salt particles used in the positive electrode materials of Examples 1 to 12 is 3 m 2 / g~8m 2 / g, or the BET specific surface area of the second lithium iron phosphate particles is less than or equal to 18.5m 2 / g, the secondary batteries prepared therefrom have both excellent energy density and cycle performance.
[0200] The molecular formula of the first lithium iron phosphate salt particle or the second lithium iron phosphate salt particle of Examples 1 to 12 is Li m Fe x P y O j Q q When Q is one or more of the elements Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, etc., and particularly preferably Mn and Ti, the secondary batteries prepared therefrom have both excellent energy density and cycle performance.
[0201] When the content of Q in the first lithium iron phosphate salt particles used in the positive electrode materials of Examples 1 to 12 is 4000ppm-10000ppm, or when the content of Q in the second lithium iron phosphate salt particles is 1000ppm-3000ppm, the secondary batteries prepared therefrom have both excellent energy density and cycle performance.
[0202] When the capacity proportion η of the first lithium iron phosphate salt particles in the positive electrode materials of Examples 1 to 12 is ≥ 88%, the secondary batteries prepared therefrom have both excellent energy density and cycle performance.
[0203] The surface density of the positive electrode active material on one side of the positive electrode sheets of Examples 1 to 12 is 20.0 mg / cm 2 -35.0mg / cm 2 The secondary batteries prepared by them have both excellent energy density and cycle performance.
[0204] The compaction density of the positive electrode active material layer on the positive electrode sheets of Examples 1 to 12 is 2.35 g / cm 3 -2.70g / cm 3 The secondary batteries prepared by them have both excellent energy density and cycle performance.
[0205] It should be noted that the present application is not limited to the embodiments described. The embodiments described are only examples, and the embodiments having substantially the same structure as the technical idea and exerting the same effects within the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the subject matter of the present application, other methods of applying various modifications that can be thought of by those skilled in the art to the embodiments and combining some of the constituent elements in the embodiments to construct the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode material, characterized in that: comprising first lithium iron phosphate salt particles and second lithium iron phosphate salt particles, The primary average particle size of the first lithium iron phosphate salt particles is 500nm to 3000nm, Based on the total weight of the second lithium iron phosphate salt particles, the carbon content of the second lithium iron phosphate salt particles is 1.5 wt % to 2.0 wt %. The mass of the second lithium iron phosphate salt particles is greater than or equal to the mass of the first lithium iron phosphate salt particles.
2. The positive electrode material according to claim 1, characterized in that The mass ratio of the second lithium iron phosphate salt particles to the first lithium iron phosphate salt particles is 1:1 to 8:
1.
3. The positive electrode material according to claim 1 or 2, characterized in that The primary average particle size of the second lithium iron phosphate salt particles is 50 nm to 400 nm.
4. The positive electrode material according to any one of claims 1 to 3, characterized in that The primary average particle size of the first lithium iron phosphate salt particles is 650nm to 920nm.
5. The positive electrode material according to any one of claims 1 to 4, characterized in that Calculated based on the total weight of the first lithium iron phosphate salt particles, the carbon content of the first lithium iron phosphate salt particles is 0.8 wt %-1.5 wt %.
6. The positive electrode material according to any one of claims 1 to 5, characterized in that The second lithium iron phosphate salt particle includes a core and a carbon coating layer on at least a portion of the surface of the core.
7. The positive electrode material according to claim 6, characterized in that The carbon coating layer includes a first carbon coating layer and a second carbon coating layer, wherein the first carbon coating layer is located between the core and the second carbon coating layer.
8. The positive electrode material according to any one of claims 1 to 7, characterized in that The BET specific surface area of the first lithium iron phosphate particles is 3 m 2 / g~8m 2 / g; and / or, the BET specific surface area of the second lithium iron phosphate particles is less than or equal to 18.5m 2 / g.
9. The positive electrode material according to any one of claims 1 to 8, characterized in that: The molecular formulas of the first lithium iron phosphate salt particle and the second lithium iron phosphate salt particle are independently Li m Fe x P y O j Q q , wherein Q includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.95≤m≤1.15, 0.9≤x≤1, 0.95≤y≤1, 3.5≤j≤4, and 0<q≤0.
1.
10. The positive electrode material according to claim 9, characterized in that wherein Q comprises at least one of Ti, V, Mg, and Nb, Calculated based on the total weight of the first lithium iron phosphate salt particles, the content of Q in the first lithium iron phosphate salt particles is 4000ppm-10000ppm; and / or, Calculated based on the total weight of the second lithium iron phosphate salt particles, the content of Q in the second lithium iron phosphate salt particles is 1000ppm-3000ppm.
11. The positive electrode material according to any one of claims 1 to 10, characterized in that The positive electrode material is single crystal particles and / or polycrystalline particles.
12. The positive electrode material according to any one of claims 1 to 11, characterized in that The capacity proportion η of the first lithium iron phosphate salt particles is ≥ 88%, and η is defined as: A battery containing the first lithium iron phosphate salt particles as a positive electrode material is charged and discharged twice at a constant current rate of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current rate of 1C. In the charge and discharge test at a rate of 1C, the capacity value at a discharge voltage of 3.2V is extracted as C1, and the capacity value at a discharge voltage of 2.0V is extracted as C2, η=C1 / C2, wherein the charging process includes constant voltage charging, a constant voltage of 3.75V, and a constant voltage cut-off current of 50μA.
13. A positive electrode sheet, characterized in that: The positive electrode material comprises the positive electrode material according to any one of claims 1 to 12.
14. The positive electrode sheet according to claim 13, characterized in that: The surface density of the positive active material on one side of the positive electrode sheet is 20.0 mg / cm 2 -35.0mg / cm 2 .
15. The positive electrode sheet according to claims 13 to 14, characterized in that: The compaction density of the positive electrode active material layer on the positive electrode sheet is 2.30 g / cm 3 -2.70g / cm 3 .
16. A secondary battery, characterized in that: A positive electrode sheet comprising any one of claims 13 to 15.
17. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 16.
Citation Information
Patent Citations
High-compaction-density lithium iron phosphate and preparation method thereof
CN107256968A
Lithium iron phosphate positive pole piece and preparation method and application thereof
CN113422049A
Lithium iron phosphate positive plate, preparation method and lithium iron phosphate lithium ion battery
CN113451548A
Lithium iron phosphate positive electrode active material, preparation method thereof, positive electrode plate and battery
CN114068919A
Carbon-coated lithium iron phosphate positive active material, preparation method thereof, positive pole piece containing carbon-coated lithium iron phosphate positive active material and lithium ion battery
CN116601798A
Cited By
Battery
CN121123271A